Mediastinitis and retropharyngeal abscess following delayed diagnosis of glass ingestion. Issue 2 (26th January 2006) - Allotey, J; Duncan, H; Williams, H
Abstract : Foreign body ingestion is a common occurrence in childhood. We report the outcome of an infant who swallowed a piece of glass. The absence of a foreign body on chest radiograph led to delayed diagnosis and then to the well documented complications of retropharyngeal abscess and mediastinitis. She was admitted to the paediatric intensive care unit a week after her initial presentation, subjected to multiple invasive and non-invasive procedures, and 6 weeks after her initial presentation to the accident and emergency department, was discharged back to her referring hospital having re-established oral feeds.